STRATEGI JURNAL PREDATOR MENGUNDANG PUBLIKASI MELALUI EMAIL: MENGAJAK KONTRIBUSI DALAM KONFERENSI DAN PUBLIKASI JURNAL, APAKAH TERJEBAK? - Agung, Pangestu; Rosyid Ridlo, Al Hakim; Yanuar Zulardiansyah, Arief; Hexa Apriliana, Hidayah; Aviasenna, Andriand (STIKES KESDAM IV/DIPONEGORO, 2023)
Scientific publications are a challenge to disseminate information on research results to scientific audiences. Often authors are required to choose several publication options, including conference proceedings to journal articles. Nowadays, there has been a rise in scientific publications with fast-track slogans, both at low cost and tremendous cost. Authors often get emails from certain editors inviting them to contribute to scientific publications through conferences and journals. Both of these strategies are used through the email addresses of authors who have published scientific papers before so that email addresses are easily obtained for scientific invitations. We received invitations from medical journal editors to contribute to their international conferences, as well as including invitations to publish journal articles in their journals. The publication cost offered is quite fantastic. If choosing the option of publication to a journal is not carefully, it is feared that it would be stuck with this strategy. A simple strategy is through a search engine with the journal name, one of the portals that provide discussions in the form of a Research Gate. Our findings can serve as advice for authors who want to publish their scientific work in journals with high scientific integrity and undergo a rigorous peer review process.